+0  
 
+1
803
1
avatar

A = B                        I xA

a² = AB                     I + a²-2AB

A²+A²-2AB = A²-AB   I : (A²-AB)

 

2=1

 

:P

 03.12.2015

Beste Antwort 

 #1
avatar+26318 
+5

A = B                        I xA

a² = AB                     I + a²-2AB

A²+A²-2AB = A²-AB   I : (A²-AB)

2=1

 

Man darf nicht durch 0 teilen! \((A^2-AB) \ne 0\)

 

Da A=B ist, ist \((A^2-AB) = (A^2-A\cdot A) = (A^2-A^2) = 0\)

 

laugh

 04.12.2015
 #1
avatar+26318 
+5
Beste Antwort

A = B                        I xA

a² = AB                     I + a²-2AB

A²+A²-2AB = A²-AB   I : (A²-AB)

2=1

 

Man darf nicht durch 0 teilen! \((A^2-AB) \ne 0\)

 

Da A=B ist, ist \((A^2-AB) = (A^2-A\cdot A) = (A^2-A^2) = 0\)

 

laugh

heureka 04.12.2015

7 Benutzer online